The Sexual Risk Order and the Sexual Harm Prevention Order: the first two years - Kingston, Sarah (Probation journal, 2018)
We now have two years’ experience of the Sexual Risk Order and the Sexual Harm Prevention Order, being the two civil orders brought in to replace and consolidate the old Sexual Offences Prevention Orders (SOPO), the Risk of Sexual Harm Orders (RSHO) and the Foreign Travel Order (FTO). This article looks at the background to these orders that have given the police new powers and the process by which the law was changed to bring in the new orders.